Clinical Review of Safety and Outcomes in Minimally Invasive Thyroid Surgery - Rudi Haris Munandar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Thyroid cancer is one of the most common endocrine malignancies, with surgery remaining the cornerstone of its management. Conventional open thyroidectomy, although oncologically effective, is often associated with postoperative morbidity, prolonged recovery, and cosmetic concerns. These limitations have driven the development of minimally invasive thyroid surgery (MITS) as an alternative approach. This study aims to clinically review the safety, effectiveness, and postoperative outcomes of MITS in the management of thyroid cancer. A clinical review was conducted by analyzing relevant peer reviewed studies published in international databases, focusing on surgical safety, oncological effectiveness, and postoperative recovery outcomes. The results indicate that MITS demonstrates a safety profile comparable to open thyroidectomy, with no significant increase in major complications such as hypoparathyroidism or recurrent laryngeal nerve injury. Oncological outcomes, including tumor control and recurrence rates, were equivalent in selected low to intermediate risk patients. Moreover, MITS consistently showed superior postoperative outcomes, including reduced pain, shorter hospital stays, faster recovery, and higher cosmetic satisfaction. These findings support MITS as a safe and effective surgical option within patient centered thyroid cancer management.